Proyecto de Factibilidad para la Implementación de una Empresa Productora y Comercializadora de Aceite de Menta, en la Ciudad de Loja - Toala Guevara, María Lizeth (2016)
This thesis main objective is to "determine the feasibility of creating a production and marketing company peppermint oil, in the city of Loja", based on market research, technical and financial. Loja has a cold climate for the cultivation of mint, therefore the production of this plant is abundant, same that is not utilized in full, also offers several benefits for our beauty as for our body, it can use as analgesic, freshener, moisturizing, massage therapy, stimulant, digestive infusions, respiratory problems among others. Currently, the Loja's public does not know about the benefits of this plant, besides that it can get peppermint oil, to solve this problem, the present project the following objectives: to conduct a market study to identify the demand and supply of the product (peppermint oil); conduct a technical study to determine the capabilities, size, location and product engineering, likewise design the organizational and legal structure for the new company; develop a financial study to establish the amount of investment and financing, cost analysis, establishment of revenue and the statement of income or expense of the project, finally make the financial evaluation of the company, using all indicators as the net present value, internal rate of return, cost benefit ratio, sensitivity analysis, and capital recovery period for determining the profitability of the project. Deductive and inductive method, with which was determined generally and specific needs: the goals set methodology, same that allowed outline the steps, making references 6 to the methods and techniques used, such as continued consumers about the product. The survey technique was applied to the families of the city of Loja, which for 2015 are 48,518 families in obtaining a sample size of 381 surveys. With the results, the potential which is 60% of families earning 29 111 potential claimants, demand identifying 30% of these claimants are real that the quantity is 8,733 families, effective demand is represented by 78% the actual number of applicants with 6.81 families. As for the technical study, both installed capacity used was determined as being the used capacity 23,088 bottles a total of 50 ml of peppermint oil per year. The company will be incorporated as "MINT GOUT FRAIS CIA. LTDA ". The investment amount is $ 13,765.03 to be funded 60% by domestic capital, amounting to a value of 8281.90 and 40% by a financial institution is $ 5,483.00. With cost analysis depreciation, reinvestment, production costs and operating costs, leading to administrative expenses, selling expenses, financial and other expenses, is structured budget proformado obtaining a unit production costs of $ 2 was determined 20 and with reference to the competition and a profit margin of 18% a selling price of $ 2.60 which brings us to earn an income of $ 60,028.80 in the first year was established. financial assessment as it was determined that the net present value exceeds investment, therefore the project is feasible was made. 7 The project is profitable and an internal rate of return of 51.18% is obtained indicating that the money invested pays a higher rate, compared with the interest rate of the bank loan is 10%.